Financial literacy among children in Kedah - Muhammad Faris, Omar (2020)
The bankruptcy case and financial literacy seems to be a serious issues in Malaysia. Bank Negara Malaysia (BNM) reported that level of financial literacy among Malaysian was at 36% compared to other developed country at 59%. While, the number of bankruptcy cases continuously increases from year to year. Thus, in order to overcome this issues BNM launched the "5 Years National Strategy for Financial Literacy" programme from 2019- 2023 by nurturing the values start from school children. In order to ensure this program successfully implemented, a further study require to measure the determinants factor toward children financial literacy. Thus, the main objective of this thesis is to identify the level of children financial literacy in Kedah and analyze the significant factors that influenced their level of financial literacy. In order to achieve the research objective, this study surveyed 320 primary school students in Kedah, aged from 7 to 12 years old using both face to face and online method. The measurement of the level of children financial literacy based on passing rate indicator provided by Chen, Volpe and Pavlicko (1996); where >80% is high level of financial literacy, 60%-79% is moderate level of financial literacy and below 60% is low level of financial literacy. Results show that children in Kedah are highly financially literate. Besides that, there are significant differences in children financial literacy according to their parent education level, parental income, students class group and school location. Based on linear regression model, results showed saving behavior (SAVING), spending behavior (SPENDING), parent role (PARENT), peer role (PEER), school involvement (SCHOOL) and technology (TECH) are significantly influenced children financial literacy. Findings of the study are aligned with Family Financial Socialization Agents Theory and Consumer Socialization Agents Theory. Thus, by providing the results of this study it hope that an authority body could play their role to nurture the importance of financial literacy among children to curb the issues of bankruptcy in Malaysia.